Boosting Tax Compliance through Education in Indonesia: Meningkatkan Kepatuhan Pajak melalui Pendidikan di Indonesia - Pratama, Riang; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the factors affecting boarding house tax compliance in Candi District, Sidoarjo Regency. Despite the high tax potential, many business owners neglect their tax obligations. Using a quantitative descriptive approach, data were collected from 33 boarding house owners via questionnaires and analyzed using multiple linear regression. Results indicate that taxpayer knowledge, understanding, and awareness significantly enhance compliance. This research highlights the need for targeted educational and awareness programs to improve tax compliance among boarding house owners in industrial areas. Highlight: High Potential: Industrial area boarding house taxes are significantly underutilized. Key Factors: Knowledge, understanding, and awareness boost taxpayer compliance. Policy Implications: Educational programs improve tax compliance in industrial areas. Keyword: tax compliance, boarding houses, taxpayer knowledge, Sidoarjo, quantitative analysis